2009
DOI: 10.1097/qai.0b013e3181a4f53e
|View full text |Cite
|
Sign up to set email alerts
|

High HIV Prevalence Detected in 2006 and 2007 Among Men Who Have Sex With Men in China's Largest Municipality: An Alarming Epidemic in Chongqing, China

Abstract: Urgent attention for prevention services is required to address the overall high HIV prevalence among MSM in the city, with special focus on subgroups as older, married MSM, and those recruited from bathhouses and saunas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 16 publications
6
66
0
1
Order By: Relevance
“…In some Chinese cities, the HIV prevalence among MSM has been higher than 10% and the prevalence of syphilis has been close to 20% [3][4][5][6][7][8][9]. There is a general consensus that evidencebased HIV interventions targeting MSM are greatly warranted in China.…”
Section: Introductionmentioning
confidence: 95%
“…In some Chinese cities, the HIV prevalence among MSM has been higher than 10% and the prevalence of syphilis has been close to 20% [3][4][5][6][7][8][9]. There is a general consensus that evidencebased HIV interventions targeting MSM are greatly warranted in China.…”
Section: Introductionmentioning
confidence: 95%
“…In Bangkok, men who have sex only with other men are more than 2.5 times more likely to be HIV-infected than men who have sex with both men and women (Li et al, 2009). While one study in Jinan, China, found that unmarried men who have sex only with other men were more than six times more likely to be HIV-infected than married men with both male and female partners (Ruan et al, 2009), another survey in Chongqing, China, determined that married men who have sex with men were more than twice as likely to be infected as their non-married counterparts (Feng et al, 2009 Ma et al, 2007;Mansergh et al, 2006). In a survey in the Lao People's Democratic Republic, for example, fewer than one in four men who have sex with men reported consistent condom use with nonregular partners (Sheridan et al, 2009).…”
Section: Men Who Have Sex With Menmentioning
confidence: 99%
“…In a region where overall HIV prevalence is low, high levels of infection among men who have sex with men have been (Chemnasiri et al, 2008), 12.5% in Chongqing, China (Feng et al, 2009), between 7.6% and 18.1% in a study of over 4500 self-identified men who have sex with men in southern India (Brahmam et al, 2008) Figure 12) (Ma et al, 2007).…”
Section: Men Who Have Sex With Menmentioning
confidence: 99%
“…The review presented by Beyrer (2010) reveals the deficiencies in taking care of MSM in developing countries. The growing concern of HIV transmission by MSM in China is discussed by Feng et al (2009). A study from China indicated that the HIV + rate of MSM in Beijing was 4.6% (2.2%-7.6%) and of those 56.3% (50.9%-62.5%) were reported having had a bisexual sex preference (Ma et al, 2007).…”
Section: "Actors" Responsible For Spreading Hivmentioning
confidence: 99%